Assessment of Cytotoxicity on Moringa Olifera Against Ehrlich Ascites Carcinoma in Swiss Albino Mice - Devi T, Gokila; Suryadevara S, Nagaraja; L R, Gopinath (Asian Pacific Journal of Cancer Biology, 2017)
Objective: The present study determines the potent cytotoxic and antitumor properties of methanolic extract of Moringa oleifera leaves. Material and Method: The leaves were collected from in and around Tiruchengode of Nammakal district of Tamilnadu. The collected leaves were shade dried and powdered and the Methanolic extract was extracted using the soxhlet apparatus. In-vitro cytotoxicity study was done by Tryphan Blue Dye Exclusion method and MTT (3-(4, 5-dimethyl thiazolyl-2)-2, 5- diphenyltetrazolium bromide) assay. In short-term cytotoxicity study by Tryphan Blue Dye Exclusion method the IC50 value against EAC cell lines was found to be 163.91 µg/ml. In Long-term cytotoxicity study by MTT assay the IC50 value against Normal Mouse Embryonic Fibroblast (NIH 3T3) was found to be 260.85 µg/ml for Human Cervical Cancer cells (HeLA) was 182.41 µg/ml for Human Laryngeal Epithelial Carcinoma (HeP-2) was 195.93. µg/ml and for Human Liver Cancer cells (HepG2) was 168.61 µg/ml. The MST of the control group was 17.33 ± 1.53 days, whereas it was 43.67 ± 1.15, 23.67 ± 1.53 and 33.33 ± 1.53 days for the groups treated with MMO (200 and 400mg/kg) and 5 FU respectively (0.001 & 0.001). The increase in lifespan of Tumour-bearing mice treated with MMO and 5-FU was found to be 36. 75, 92.78 and 152.84 respectively. Result: Haematological parameters of a tumour bearing mice on the day 14 were showed significant changes when compared to normal mice. The total WBC count, protein and PCV were found to increase with a reduction in the hemoglobin content of RBC. At the same time interval, MMO (200 and 400mg/kg) treatment could change these parameters near normal. Maximum alternation occurred in the MMO treatment at the dose of (400mg/kg). There was the significant reduction in the Tumour volume of mice treated with MMO (200 and 400 mg/kg/p.o.). The Tumour volume of control animals was 2. 92 ± 0.12 ml where it was 2.55 ± 0.11 ml and 1.82 ± 0.04 ml for the groups treated with MMO (200 and 400mg/kg/p.o) respectively (P < 0.01 & 0.005). Coclusion: The present study provides clear evidence, that the extract of Moringa olifera shows effective cytotoxicity against Ehrlich ascites carcinoma (EAC) cells in Swiss albino mice. A further study about the active principles and mechanism of action of the Methanolic extract of Moringa oleifera at the molecular level was needed.